Personalised pulmonary rehabilitation in COPD - Emiel F.M. Wouters; Birgit B.R.E.F. Wouters; Ingrid M.L. Augustin; Sarah Houben-Wilke; Lowie E.G.W. Vanfleteren; Frits M.E. Franssen (European Respiratory Review, 2018)
This review summarises ongoing developments in personalised medicine and individualised medicine in chronic obstructive pulmonary disease (COPD). Currently applied classification systems largely ignore the complexity and heterogeneity of the COPD syndrome. Personalised medicine has to consider the influence of unique circumstances of the person, which contribute to this heterogeneity and complexity. Pulmonary rehabilitation is described as a comprehensive, individualised intervention based on thorough assessment of identifiable treatable traits. Partnership in care will become a crucial factor to improve and maintain health. Tolerating uncertainty and unpredictability will enrich future doctor–patient relationships.